Proposal for process improvement in the ceramic coating process applying DMAIC method - Araújo, Túlio Oliveira; Lira, Taisa Shimosakai de; Xavier, Thiago Padovani (Latin American Journal of Energy Research, 2024)
Brazil plays a prominent role in the global ceramic coatings market, and since the beginning of production within the country, there has been a recognized need for innovation in Brazilian industries to maintain competitiveness. This case study aims to describe the utilization of Lean Six Sigma methodology concepts, specifically focusing on the DMAIC phase, for improving a process in a porcelain and ceramic coatings industry. The “Classification” sector was selected to apply the DMAIC method due to the dynamic nature of the processes involved in this phase of production, which has teams that are more receptive to changes in the work routine, with the aim of achieving superior performance more quickly. The implemented process changes yielded noticeable results and were acknowledged by the sector management, as they brought significant gains in terms of efficiency, quality, and organization. The application of the DMAIC methodology proved to be comprehensive and flexible, enabling effective adaptation to the specific context of this industry.